Co/ZrO2, Co/CeO2 and MnCoCe structured catalysts for COPrOx - Gómez, Leticia Ester (2013)
Cordierite monoliths washcoated with MnCoCe(CP), Co(I)/ZrO2 and Co(I)/CeO2 catalysts were prepared and studied for the CO preferential oxidation (COPrOx) reaction. Among them, the MnCoCe/M system presented the best CO conversion at low temperatures and the Co(I)/CeO2-M catalyst, the best selectivities toward CO2. In the three catalysts, Co3O4 was the main Co containing compound and it was the active species for the COPrOx reaction. Nevertheless, the Co(I)/CeO2-M and MnCoCe/M solids resulted moreactive than Co(I)/ZrO2-M, possibly due to the better redox properties of the ceria. In the MnCoCe/Mcatalyst prepared by co-precipitation, the addition of Mn represented an additional positive effect. Thepresence of Mn promoted the re-oxidation of Co2+to Co3+and, consequently, the activity increased atlow temperature. It is also shown that homogeneous and mechanically stable coatings on the walls of the three monolithic catalysts were obtained, which in turn yielded promising results in the COPrOx reaction.